2017
DOI: 10.5435/jaaos-d-16-00548
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Utility of Synovial Fluid Markers in Periprosthetic Joint Infection: A Systematic Review and Meta-analysis

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
0
28
0
2
Order By: Relevance
“…Although there is an international consensus for the definition of PJI, no single “gold standard” test currently exists for diagnosing PJI. Recently, many studies have reported the usefulness of synovial fluid cytokines—such as interleukin-6, c-reactive protein, and alpha-defensin—as alternative and better diagnostic markers for PJI compared to the standard technique [ 7 , 8 , 18 21 ]. The overall sensitivity and specificity of these markers were more than 80% and 90%, respectively [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is an international consensus for the definition of PJI, no single “gold standard” test currently exists for diagnosing PJI. Recently, many studies have reported the usefulness of synovial fluid cytokines—such as interleukin-6, c-reactive protein, and alpha-defensin—as alternative and better diagnostic markers for PJI compared to the standard technique [ 7 , 8 , 18 21 ]. The overall sensitivity and specificity of these markers were more than 80% and 90%, respectively [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies regarding the new diagnostic techniques demonstrated that some biomarkers—such as procalcitonin (PCT), interleukin-6 (IL-6), and α -defensin—are helpful and a better marker for PJI [ 4 6 ]. Moreover, several studies also showed that the synovial fluid biomarkers obtained directly from the infected joint are more reliable and accurate for diagnosing PJI compared to serum biomarkers and other existing tests [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused their analysis on synovial CRP, leukocyte esterase, interleukin-6 (IL-6), interleukin-17 (IL-17) and α-defensin. 26 We have been using quantitative synovial CRP (with a threshold level of 9.5 mg/L) as it is as useful as a frozen section to diagnose PJI; synovial CRP and intraoperative frozen section have a similar sensitivity, specificity and predictive value. 27 , 28 Since synovial CRP is easier to obtain, less expensive and less dependent on the technique of obtaining and interpreting a frozen section, we prefer it to the latter to use on a daily basis.…”
Section: Synovial Biomarkersmentioning
confidence: 99%
“…Nonetheless, we are aware that synovial CRP may result in higher numbers of false positives when compared to α-defensin or IL-17, despite the three of them being of high diagnostic utility. 26 …”
Section: Synovial Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation